ChemInform Abstract: Synthesis of Stoichiometric and Bulk CrN Through a Solid‐State Ion‐Exchange Reaction. Issue 13 (18th March 2013) - Chen, Miao; Wang, Shanmin; Zhang, Jianzhong; He, Duanwei; Zhao, Yusheng
Abstract Phase‐pure, stoichiometric, and well‐crystallized bulk CrN is prepared from powders of Na2CrO4 and hexagonal BN in a molar ratio of 1:2 by a solid state ion‐exchange route under high pressure (5 GPa, 1200 °C).